(untitled) (Pesticides and Phytomedicine / Pesticidi i fitomedicina, 2012)
Entomofaunistic studies contain a large number of data regarding the number of collected species, the number of individuals within species, time of collection, localities, species biology and morphology natural enemies and hosts. Besides thematic and temporal components this kind of studies include spatial component which is crucial for the use of GIS methodology and advanced possibilities of geospatial analysis. During our studies on jumping plant lice (Psylloidea) fauna and their natural enemies on the territory of Serbia which lasted for several years, a large number of spatially referenced data related to this group of insects were collected. The process of collecting, archiving and classifying the data on each species was improved by applying the GIS methodological approach after which the data were entered into database. The analysis of data using thematic and spatial queries, as well as graphic, numeric and textual display of the results from studies enabled simpler and more complete survey of horizontal and vertical distribution of jumping plant lice, their biology and relationship with plants, predators and parasitoids.